PROBLEMY NORMALIZACJI I KODYFIKACJI W HISTORII JĘZYKA DOLNOŁUŻYCKIEGO I JĘZYKA GÓRNOŁUŻYCKIEGO - LEWASZKIEWICZ, TADEUSZ (Slavia Occidentalis, 2020)
The subject of the article is a process of standardisation and codification of the Upper Sorbian and Lower Sorbian languages. The author enumerates and reviews the most important grammars and dictionaries codifying the Sorbian language, stresses the influence of the Maćica Serbska cultural and educational associations on arriving at a common Upper Sorbian standard and demonstrates the role of the Czech language in developing Sorbian standards.